Model Kooperatif Tipe Index Card Match dalam Meningkatkan Hasil Belajar peserta didik SMK Kelas XI ATPH Materi Menghitung Kebutuhan Pupuk - Isna Khofifah Assyfa; Sukian Wilujeng; Maureen Evita (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Fertilization is one of the essential aspects of plant care. It should be carried out in a balanced manner, adjusted to the nutritional needs of the plant. A balanced fertilizer application can positively affect plant growth. This study used the Classroom Action Research method developed by Stephen Kemmis and Robin McTaggart. It was conducted in class XI ATPH 3 at SMKN 1 Purwosari, focusing on the fertilization component of the Fertilization Needs material. The results showed that the Index Card Match Cooperative Learning Model can increase students' learning motivation. Students became more active in every learning activity, including solving problems, discussing with peers, and asking questions to the teacher. Regarding learning outcomes, the Index Card Match Cooperative Learning Model improved the percentage of students who passed classically—from 30.30% in the pre-cycle, to 69.70% in cycle 1, and further increased to 84.85% in cycle 2.